Dari Jejak Cheng Ho hingga Kerja Sama Internasional: Analisis Paradiplomasi dalam Sister City Semarang–Fuzhou - Reyva Alviona Fernanda Priskilla (Lenggogeni Data Publishing, 2026)
This study aims to analyze the implementation of the sister city partnership between the City of Semarang and the City of Fuzhou, China, which has continued despite the absence of a Memorandum of Understanding (MoU) as a formal legal basis. The research employs a qualitative method, with data collected through interviews and document analysis. The analysis is conducted using the concepts of paradiplomacy and sister city cooperation.The findings indicate that the implementation of the Semarang–Fuzhou sister city partnership has been successfully realized through various activities in the fields of economy, education, culture, and tourism. In the economic sector, cooperation has been carried out through investment promotion and commodity exports. In the field of education, collaboration has included student exchange programs, teacher exchanges, seminars, and knowledge-sharing activities. Meanwhile, cooperation in culture and tourism has been strengthened through the preservation of Chinese historical heritage and the organization of cultural festivals. The study further reveals that shared historical and cultural backgrounds, along with the support of the local Chinese community, have been important factors contributing to the success of the partnership. Therefore, paradiplomacy can be effectively implemented through concrete collaborative activities even in the absence of a formal framework in the form of an MoU. Abstrak Penelitian ini bertujuan menganalisis implementasi kerja sama sister city antara Kota Semarang dan Kota Fuzhou, Tiongkok, yang tetap berlangsung meskipun belum didukung oleh Memorandum of Understanding (MoU) sebagai dasar hukum formal. Penelitian menggunakan metode kualitatif dengan teknik pengumpulan data melalui wawancara dan studi dokumentasi. Analisis dilakukan menggunakan konsep paradiplomasi dan sister city. Hasil penelitian menunjukkan bahwa implementasi sister city Semarang–Fuzhou berhasil diwujudkan melalui berbagai kegiatan di bidang ekonomi, pendidikan, budaya, dan pariwisata. Pada bidang ekonomi, kerja sama diwujudkan melalui promosi investasi dan ekspor komoditas. Pada bidang pendidikan, kerja sama dilakukan melalui pertukaran pelajar, pertukaran guru, seminar, dan berbagi pengetahuan. Sementara pada bidang budaya dan pariwisata, kerja sama diperkuat melalui pelestarian warisan sejarah Tionghoa dan penyelenggaraan festival budaya. Temuan penelitian menunjukkan bahwa kesamaan sejarah, budaya, serta dukungan komunitas Tionghoa lokal menjadi faktor penting dalam keberhasilan kerja sama tersebut. Dengan demikian, paradiplomasi dapat berjalan secara efektif melalui implementasi kegiatan konkret meskipun belum memiliki landasan formal berupa MoU. Kata Kunci: Paradiplomasi, Sister City, Semarang, Fuzhou, Kerja Sama Daerah.